1997
DOI: 10.1074/jbc.272.41.25500
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of PBP, a Protein That Interacts with Peroxisome Proliferator-activated Receptor

Abstract: In an attempt to identify cofactors that could possibly influence the transcriptional activity of peroxisome proliferator-activated receptors (PPARs), we used a yeast two-hybrid system with Gal4-PPAR␥ as bait to screen a mouse liver cDNA library and have identified steroid receptor coactivator-1 (SRC-1) as a PPAR transcriptional coactivator. We now report the isolation of a cDNA encoding a 165-kDa PPAR␥-binding protein, designated PBP which also serves as a coactivator. PBP also binds to PPAR␣, RAR␣, RXR, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
254
2
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 320 publications
(269 citation statements)
references
References 52 publications
9
254
2
4
Order By: Relevance
“…The best characterized of these is the TRAP⅐DRIP⅐ARC complex, which enhances the transcriptional activities of nuclear receptors and other signal-dependent transcription factors in vitro (29 -31). The TRAP⅐DRIP⅐ARC complex is recruited to nuclear receptors in a ligand-dependent manner via a 220-kDa component referred to as PBP/TRAP220/DRIP205, which contains two alternatively utilized LXXLL nuclear receptor interaction motifs (32,33). Disruption of the TRAP220/PRIP205/ PBP gene in the mouse results in embryonic lethality at embryonic day 11.5, and initial studies in myocyte enhancer factors have suggested a defect in ligand-dependent thyroid hormone and PPAR␥ receptor function (31,32).…”
Section: The Trap⅐drip⅐arc Complexmentioning
confidence: 99%
“…The best characterized of these is the TRAP⅐DRIP⅐ARC complex, which enhances the transcriptional activities of nuclear receptors and other signal-dependent transcription factors in vitro (29 -31). The TRAP⅐DRIP⅐ARC complex is recruited to nuclear receptors in a ligand-dependent manner via a 220-kDa component referred to as PBP/TRAP220/DRIP205, which contains two alternatively utilized LXXLL nuclear receptor interaction motifs (32,33). Disruption of the TRAP220/PRIP205/ PBP gene in the mouse results in embryonic lethality at embryonic day 11.5, and initial studies in myocyte enhancer factors have suggested a defect in ligand-dependent thyroid hormone and PPAR␥ receptor function (31,32).…”
Section: The Trap⅐drip⅐arc Complexmentioning
confidence: 99%
“…Human RB18A shared structural, gene localization and functional properties with other cellular components, as 165 kDa murine PBP (peroxisome proliferator-activated receptor (PPAR)-binding protein), which acted as a co-activator of nuclear receptors (Zhu et al, 1997). TRAP220 (Yuan et al, 1998a,b) and DRIP205 , two human genes identi®ed later than RB18A, also shared up to 98% identity with RB18A nucleotide sequence.…”
mentioning
confidence: 99%
“…TRAP220, a 220 kDa thyroid hormone receptor-associated protein (Yuan et al, 1998a,b) and DRIP205, a 205 kDa vitamin D receptor interacting protein , both belong to multiple 12 to 15 subunit complexes, namely TRAP and DRIP complexes respectively. As PBP (Zhu et al, 1997), TRAP220 (Yuan et al, 1998a;Ito et al, 1999) and DRIP205 directly interacted, through two di erentially preferred LXXLL regions (Ren et al, 2000), with distinct hormoneactivated nuclear receptors: i.e. thyroid hormone receptor (THR), vitamin D receptor (VDR), retinoic acid receptor alpha (RARa), retinoic X receptor (RXR), RORa , PPARg (Kodera et al, 2000) and glucocorticoid or estrogen receptors (Burakov et al, 2000;Warnmark et al, 2001).…”
mentioning
confidence: 99%
“…PBP/TRAP220/DRIP205, a component of the DRIP/TRAP complexes, also interacts with liganded NRs through LXXLL motifs (15,54,72). These complexes are related to the yeast SRB/Mediator complex and were identified through biochemical purification using ligand-bound VDR (DRIP) and TR (TRAP).…”
mentioning
confidence: 99%